Pembelajaran Ekstrakurikuler Kaligrafi terhadap Motorik Halus Anak Usia Dini di RA PSM Kanigoro Kras Kediri - Lailiyah, Irfatul (ACIECE, 2019)
Extracurricular learning is a program held to develop the abilities and interests of students that are carried out outside of classroom learning activities. Extracurricular learning to drawcalligraphy is one of several programs held by RA PSM Kanigoro in optimizing aspects of thedevelopment of their students. The results of data analysis show that the implementation ofextracurricular activities in drawing calligraphy is carried out every Tuesday at 10.30 until 11.30. Students who take part in extracurricular learning activities to draw calligraphy are 15 (fifteen) children consisting of 7 (seven) boys and 8 (eight) girls. This study aims to determine the use of calligraphic extracurricular activities on fine motor in early childhood. This study uses a qualitative approach, data collection techniques using the method of observation, interviews and documentation. Based on the results of interviews and observations conducted showed that children who take part in the learning activities of calligraphy are good at drawing calligraphy, are good at drawing frames and coloring calligraphy, and these activities can instill confidence in children when taking part in drawing and coloring competitions